Breeding of winter wheat varieties to create slow poazhenie to liststebelnym diseases (Eurasian Journal of Ecology, 2016)
The article presents the results of years of work (1990-2010) on the selection of winter wheat using natural and artificial backgrounds infectious infection in populations of hybrids (5900-F2-F8). As a result of breeding work identified three varieties of "donors" soft winter wheat: Almali Naz, Arap having zamelennymi types defeat to LEAFY diseases. They are currently in the selection process ispolzuyuetsya as a donor to lisostebelnym diseases.
Keywords: selection; immunity; crossover; testing